1995
DOI: 10.1111/j.1467-9507.1995.tb00059.x
|View full text |Cite
|
Sign up to set email alerts
|

Children's awareness of which peers like them and which peers dislike them

Abstract: The present research examined children's awareness of the specific same-sex peers who like or dislike them. Awareness was evaluated in relation to children's peer sociometric status. All children in grades one through six provided same-sex peer sociometric nominations and same-sex peer sociometric ratings to determine their sociometric status. In addition, each child indicated the nominations and ratings they believed they received from same-sex peers. Children's sociometric status was associated with their aw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
1
4

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 54 publications
2
26
1
4
Order By: Relevance
“…Os dados relativos à escolha mútua que revelaram que as meninas superaram os meninos neste aspecto são compatíveis com a maior facilidade de integração social no gênero feminino: indubitavelmente, há maior facilidade na interação quando existe reciprocidade e correspondência de afetos. Ainda no que diz respeito às escolhas mútuas e coerentemente com a hipótese de que as crianças populares são mais conscientes de sua própria competência social (MacDonald & Cohen, 1995), as crianças do grupo popular apresentaram maior reciprocidade nas escolhas mútuas positivas que os demais grupos.…”
Section: Preferência Rejeição Social E Avaliação De Características unclassified
“…Os dados relativos à escolha mútua que revelaram que as meninas superaram os meninos neste aspecto são compatíveis com a maior facilidade de integração social no gênero feminino: indubitavelmente, há maior facilidade na interação quando existe reciprocidade e correspondência de afetos. Ainda no que diz respeito às escolhas mútuas e coerentemente com a hipótese de que as crianças populares são mais conscientes de sua própria competência social (MacDonald & Cohen, 1995), as crianças do grupo popular apresentaram maior reciprocidade nas escolhas mútuas positivas que os demais grupos.…”
Section: Preferência Rejeição Social E Avaliação De Características unclassified
“…Research on hostile attribution biases has demonstrated that rejected and aggressive youth are especially prone to misattribute benign social cues as due to hostile intent (e.g., Dodge, Bates, & Pettit, 1990). Zakriski and Coie (1996) revealed that rejected and aggressive youth demonstrate considerable difficulty discerning which of their peers may like or dislike them (see also MacDonald & Cohen, 1995). Research also has consistently demonstrated that these youths are prone to overestimate their own social competence and status among peers (Hughes, Cavell & Grossman, 1997;Rudolph & Clark, 2001).…”
mentioning
confidence: 93%
“…Other peer acceptance measures commonly used in the literature (e.g., “who do you like the most at school?”) also capture both established and desired associations with peers (c.f., Lease & Axelrod, 2001; MacDonald & Cohen, 1995). …”
Section: Methodsmentioning
confidence: 99%